Umami Flavor Formulation of Agarwood Leaf Extract Powder - RAMIZU, NAJWA UMAIRAH; A.TALIP, BALKIS (Enhanced Knowledge in Sciences and Technology, 2024)
Fragrant, black, and resinous, agarwood (Aquilaria spp.) is utilised in manyproducts, such as oils, incense, and perfumes. It has been utilised formedicinal purposes for thousands of years and is also employed intraditional medicine. One of the priciest non-timber wood products availableworldwide is agarwood. Thus, another choice is to use the agarwood leavesbecause it is easier to find to be used in a variety of products. Although thisleaf extract has been processed into a powder, the powder has an unpleasant,bitter taste. Therefore, the goal of this project is to transform the bitter tasteof agarwood leaves into an umami taste and make them taste moreappetising. Along with sweet, salty, sour, and bitter, the five basic flavoursare umami, or savoriness. Bromelain enzyme has been used in the enzymehydrolysis process to extract the umami flavour from this powder. Followingthat, three sample formulations were made which is formulation one with83.71% agarwood powder, 8.37% salt, 3.96% sugar and 3.96% sodiumbenzoate. The second formulation with the percentage of agarwood powder93.91%, 3.13% salt, 1.48% sugar and 1.48% sodium benzoate and the lastformulation is formulation 3 with 96.25% agarwood powder, 1.93% salt,0.91% sugar and 0.91% sodium benzoate. These three samples will then gothrough two types of sensory evaluation, namely a 7-point hedonic test andalso a descriptive test with the aim of knowing the consumer's acceptance ofthis powder to be used in other products such as seasoning and also as a saltsubstitute. The results of this test will then be evaluated using the ANOVAtest. As a result, the best sample is the sample with the second formulationwhich uses 93.91% agarwood powder because it tastes not too salty and nottoo bitter with a mean score of 6.26 ± 0.876.